Comparison of effectiveness between modified transvaginal mesh surgery and vaginal pessary treatment in patients with symptomatic pelvic organ prolapse. Issue 1 (14th September 2021) - Kinjo, Manami; Tanba, Mitsuko; Masuda, Kazuki; Nakamura, Yu; Tanbo, Mitsuhiro; Fukuhara, Hiroshi
Abstract: Objectives: This study aimed to compare the efficacy of modified transvaginal mesh (TVM) surgery and vaginal pessary in patients with symptomatic pelvic organ prolapse (POP). Methods: We retrospectively analyzed 130 patients with symptomatic POP treated with either modified TVM (n = 62) or vaginal pessary (n = 68). To evaluate the prolapse, lower urinary tract, bowel, and sexual symptoms and prolapse‐related quality of life (QOL) were assessed using the prolapse QOL questionnaire. All questionnaires were completed before treatment and 1 year after the treatment. Results: One year after the treatment, the prolapse and voiding symptoms and all prolapse‐related QOL domains, except for the personal relationships and sleep/energy, were significantly improved in the pessary group. The prolapse, urinary storage, voiding, bowel, and sexual symptoms and all QOL domains significantly improved in the modified‐TVM group. Conclusions: Both the modified TVM surgery and vaginal pessary effectively treated prolapse and voiding symptoms and improved most of the prolapse‐related QOL domains. Modified TVM surgery was more effective in improving urinary storage, bowel, and sexual symptoms than the pessary treatment. Modified TVM seemed to position the organs more correctly to improve bladder, bowel, and sexual function than pessary insertion.